2019
DOI: 10.1103/physrevmaterials.3.084005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of synthesis conditions on the electrical resistivity of TiSe2

Abstract: Dilute impurities and growth conditions can drastically affect the transport properties of TiSe2, especially below the charge density wave transition. In this paper, we discuss the effects of cooling rate, annealing time and annealing temperature on the transport properties of TiSe2: slow cooling of polycrystalline TiSe2 post-synthesis drastically increases the low temperature resistivity, which is in contrast to the metallic behavior of single-crystalline TiSe2 due to charge doping from the residual iodine tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 40 publications
(52 reference statements)
2
5
0
Order By: Relevance
“…S I of the Supplemental Material. Our samples show a CDW transition at T CDW = 202 K consistent with high-quality samples used in other studies [8,[24][25][26][27].…”
supporting
confidence: 89%
“…S I of the Supplemental Material. Our samples show a CDW transition at T CDW = 202 K consistent with high-quality samples used in other studies [8,[24][25][26][27].…”
supporting
confidence: 89%
“…Nevertheless, a transport study has found finite resistivity in polycrystalline TiSe 2 samples at low temperature 12 , consistent with metallic behavior. The sensitivity of the low-temperature transport property on the synthesis condition 13 suggests that the observed metallic behavior in the polycrystalline sample is likely due to self-doping (see Fig. 1b).…”
Section: Introductionmentioning
confidence: 99%
“…A powder sample of TiSe 2 was synthesized via solid-state reaction. Powdered Ti and Se were weighed out in the atomic ratio of Ti : Se 1 : 2.02 and ground together in accordance with the work of Moya et al (2019). The resultant powder was sealed in a quartz tube under $3 Torr (1 Torr = 133.322 Pa) of partial argon atmosphere and heated at a rate of 323 K h À1 to 923 K. The sample remained at 923 K for 48 h before being quenched to ambient temperature.…”
Section: Methodsmentioning
confidence: 99%